Doubling of triazole resistance rates in invasive aspergillosis over a 10-year period, Belgium, 1 April 2022 to 31 March 2023 - Katrien Lagrou (Eurosurveillance)
Background Dutch national treatment guidelines for fungal infections have been adapted based on surveillance findings of triazole resistance rates >10% in Aspergillus species isolates. In Belgium, nationwide resistance data have not been collected since 2011. Aim Our objective was to evaluate changes in antifungal susceptibility among Aspergillus species isolates from patients with invasive aspergillosis. Methods Laboratories across Belgium were invited to send all clinically relevant Aspergillus species isolates from patients diagnosed with invasive aspergillosis, collected between April 2022 and March 2023, to the National Reference Centre for Mycosis at UZ Leuven for identification and antifungal susceptibility testing. Results Overall, 29 clinical laboratories contributed 309 isolates from 297 patients. Median patient age was 66 years (range: 6 months–96 years). Among isolates, 61% (189/309) were from male patients. At species level, Aspergillus fumigatus isolates predominated (278/309, 90%), with a 9.7% (27/278) triazole resistance rate, compared to the 4.6% rate found in 2011. Of 27 resistant isolates, successful Cyp51A sequencing of 26 showed 20 with the TR34/L98H resistance mechanism. Across the country, local A. fumigatus triazole resistance rates varied. Among provinces in the Flanders region, Antwerp had the highest resistance rate (15.4%: 10/65; p = 0.082), Flemish Brabant (6/48) also had a rate >10%, while Limburg (2/46) had the lowest rate. Conclusions Geographical differences in A. fumigatus triazole resistance rates stress the importance of implementing broad prospective surveillance initiatives, not limited to one region or one hospital. In Belgium, triazole resistance rates have doubled over 10 years, nearly attaining the 10% threshold, warranting re-evaluation of local empirical antifungal treatment regimen decisions.